Observational study on hand washing practice during COVID-19 pandemic among bank visitors in Gondar Town, Northwest Ethiopia. Issue 6 (18th August 2022) - Yigzaw, Niguse; Ayalew, Getnet; Alemu, Yitayal; Tesfaye, Bizuneh; Demilew, Demeke
ABSTRACT: Hand washing has received considerable attention during the COVID‐19 pandemic and it is simple, cost-effective, and one of the first lines of defenses in ceasing the spread of the current pandemic. Hence, assessing the actual hand washing practice of bank visitors during COVID-19 pandemic will have tremendous contribution in the prevention and control strategy of the disease. Observational study followed by demonstration was conducted from May 1 to June 15, 2020, among bank visitors at Gondar town. A total of 415 bank users participated in the study. Data was collected through observation using check list and pretested questioner. Bivariate and multivariate logistic regression was used to show the association between outcome variable with determinant factors. P -value <0.05 was taken as significant. A total of 415 participants were enrolled on the study. Most of the participants, 245 (59%), were males and 369 (88.9%) come from urban area. One hundred fifty one (36.4%) completed secondary school. Majority of the participants, 388 (93.5%), heard and watched proper hand washing practice. The proportion of proper hand washing performance was 21.4% before demonstration, but after demonstration, it was increased to 82.2%. Study participants aged 25–30 years, age of 31–40, married and attended college and above were found to be significantly associated with proper hand-washing practice. Overall, there was a significant change of hand washing practice after demonstration. Health education and public mass medias are needed, especially audio–visual aids are very important.